Making Students Eat Their Greens: Information Skills for Chemistry Students. - Sarah George; Tasnim Munshi (Issues in Science and Technology Librarianship)
Employers are increasingly requiring a range of "soft" skills from chemistry graduates, including the ability to search for and critically evaluate information. This paper discusses the issues around encouraging chemistry students to engage with information skills and suggests curricular changes which may help to "drip-feed" information skills into degree programs. [ABSTRACT FROM AUTHOR]